Materi Dakwah pada Grup Ban Non-Religi(Analisis Pesan Dakwah dalam Lirik Lagu Grub Band GIGI) - Acep Aripudin; M. Roiz Ridwan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
Not all aspects of music identical with caprice and banter, but they can also serve as medium of da’wah material conveyor. For example, band group lyric Fills of GIGI, of five song sample that analyzed by researcher for example: Reach for victory, I’tiraf, Peace,  Apostle pine and God. Every thing gets classified massage da’wah. With this songs Groups A Brass Band GIGI intend to give resuscitations and asking out to  fanses for always near his self on The Infinite Creator Mighty.